Is Fengshui a science or superstition? A new approach combining the physiological and psychological measurement of indoor environments - Jin, ZiKai; Juan, Yi-Kai (Building and environment, 2021)
Fengshui principles frequently play a vital role in the design of architecture and interior spaces, especially in China and other Asian countries. However, there is still much controversy over whether the Fengshui theory is a science or superstition. Only a few studies discuss whether the application of Fengshui guidelines has a direct impact on human comfort. The purpose of this study was to investigate the different psychological and psychological responses within the different Fengshui indoor environments. The Fuzzy Delphi Method (FDM) was used to construct indoor Fengshui evaluation criteria, and it was combined with Virtual Reality (VR), where two kinds of indoor Fengshui scenarios were created. The Heart Rate Variability (HRV) and Profile of Mood States (POMS) were used to assess the physiological and psychological changes in subjects in different indoor Fengshui environments. The results showed that a room with Fengshui consideration had a more positive HRV and POMS. It was inferred that indoor spaces with Fengshui consideration produced more positive emotions and that they were perceived to be a more comfortable environment, thus proving that the principles of Fengshui are, to a certain extent, scientific. •Apply Virtual Reality (VR) to create two rooms with different Fengshui scenarios.•Employ physiological and psychological measurements to verify Fengshui principles.•The room with Fengshui consideration has a more positive HRV and POMS.•Discuss the correlation between gender and Fengshui experiences.•Fengshui principles have a certain scientific nature.